Analisa pengaruh Marketing Mix dan perilaku konsumen setelah Covid-19 terhadap keputusan Impulse Buying pada Miniso Cabang Mall Ciputra Jakarta - Wardani, Widia Sentia; Sumarsid, Sumarsid; Jayadi, Jayadi; Kartikaningsih, Dewi; Yani, Ahmad; Simanjuntak, Robby (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of marketing mix and consumer behavior after COVID-19, both partially and simultaneously, on impulse buying decisions at the Miniso Mall Ciputra Jakarta Branch. The research method used is a quantitative descriptive method, namely research that describes the characteristics of an actual situation. The results of this study state that the partial test can be concluded that the marketing mix (marketing mix) partially has a significant effect on impulsive buying decisions, and consumer behavior after Covid 19 partially also has a significant effect on impulse buying decisions by consumers at Miniso Mall Ciputra Branch Jakarta, simultaneous test results, it can be concluded that simultaneously, namely the marketing mix (marketing mix), and consumer behavior after Covid 19 jointly have a significant effect on impulse buying decisions by consumers at Miniso Mall Ciputra Jakarta Branch, analysis results determination found that the role of the marketing mix (marketing mix) and consumer behavior after covid 19 contributed 51.3% to impulse buying decisions by consumers at Miniso Mall Ciputra Jakarta Branch and the remaining 48.7% was influenced by factors another factor that not careful writer, for example price, service, business competition, and quality of human resources.